Efficacy and safety of Qi and Blood Tonic Chinese Medicines in the treatment of COVID-19: A protocol for systematic review and meta-analysis. Issue 49 (9th December 2022) - Yang, Feifei; Zhang, Xiaosi; Zhang, Zhe; Lu, Hao; Li, Jiawei; Bai, Ning; Geng, Naizhi
Abstract : Background: Coronavirus disease in 2019 (COVID-19) is a sudden public event affecting all human beings, with the rapid transmission, extensive groups affected, many complications, and high mortality. Traditional Chinese Medicine has a long history of preventing and treating infectious diseases, and numerous studies have shown that Traditional Chinese Medicine, especially herbal medicine, has a positive effect on the prevention, treatment, and post-healing recovery of this COVID-19, and herbal medicines to supplement qi and blood often occupy a certain proportion of it. However, there is no relevant meta-analysis to date. Therefore, this study aims to evaluate the efficacy and safety of qi and blood tonic herbal medicines in the treatment of COVID-19 through Systematic Review and meta-analysis to provide a reference basis for widespread clinical application. Methods: We will search from the following databases for the period from the time of database construction to March 1st, 2023. The English databases include: PubMed, MEDLINE, EMBASE, Cochrane library, WOS, Google Scholar, and CENTRAL; The Chinese databases include: China National Knowledge Infrastructure, China Biomedical Literature Database, Technology Journal Database, and Wanfang. Randomized controlled trials in English or Chinese that include Chinese herbal medicines for tonifying Qi and Blood in the treatment of patients with COVID-19 will be included. Data were independently screened and collected by 2 investigators. The risk of bias for each trial was assessed using the Cochrane Risk of Bias Tool 2.0. RevMan 5.3 software was used for the meta-analysis of the data. Primary outcome indicators included cure, mortality, and exacerbation rates (change in disease severity category, patient admission to ICU, etc.). Secondary outcome indicators included recovery rate or duration of major symptoms (e.g., fever, cough, fatigue, and weakness, etc.), rate or duration of nucleic acid conversion for severe acute respiratory syndrome coronavirus-2, improvement or recovery of chest CT performance, length of hospital stay, and other adverse events. Results: This protocol adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-P guidelines to ensure clarity and completeness of reporting in all phases of the systematic review. Conclusion: This study will provide evidence regarding the efficacy and safety of Qi and Blood Tonic Chinese Medicines for the treatment of COVID-19. PROSPERO registration number: CRD42022361822 (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022361822 ).